Microinvasive carcinoma of the uterine cervix in a 14-year-old adolescent: case report and literature review - Gonçalves, Carla Vitola (2012)
Submitted by Michele Fernanda (michele_fernandas@hotmail.com) on 2012-08-24T07:53:50Z No. of bitstreams: 1 Microinvasive carcinoma of the uterine cervix in a 14-year-old adolescent.pdf: 95040 bytes, checksum: 1a57878a1848440475c163fd1c081523 (MD5)